2003
DOI: 10.1159/000073506
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Nitric Oxide Synthase Modulation of Dorsal Horn Neuronal Responses in the Rat: A Developmental Study

Abstract: Nitric oxide (NO) is a diffusible chemical messenger functionally linked to N-methyl-D-aspartate (NMDA) receptor activity and has been shown to be involved in modulating numerous pathways in the central nervous system. In order to investigate the role of the neuronal NO synthase type I (nNOS)/NO system in the postnatal development of dorsal horn nociceptive pathways in rats, the specific nNOS inhibitor 7-nitroindazole sodium salt (7-NI) and the non-specific NOS inhibitor nitro-L-arginine methyl ester (L-NAME) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…A-fiber-evoked responses and input were unaffected by L-291. These selective inhibitory effects of spinal DDAH-1 antagonism on NMDA-mediated neuronal events suggest a predominantly postsynaptic effect and are similar to those produced by spinal inhibition of nNOS, 31 , 33 as well as drugs targeting spinal NMDA receptors. 6 , 7 Targeting DDAH-1 may be a novel way of modulating the NMDA-NO signaling pathway through manipulation of an endogenous control, which may allow physiopathological signaling to be selectively modulated and so potentially increasing tolerability over direct NMDA receptor blockers.…”
Section: Discussionmentioning
confidence: 72%
“…A-fiber-evoked responses and input were unaffected by L-291. These selective inhibitory effects of spinal DDAH-1 antagonism on NMDA-mediated neuronal events suggest a predominantly postsynaptic effect and are similar to those produced by spinal inhibition of nNOS, 31 , 33 as well as drugs targeting spinal NMDA receptors. 6 , 7 Targeting DDAH-1 may be a novel way of modulating the NMDA-NO signaling pathway through manipulation of an endogenous control, which may allow physiopathological signaling to be selectively modulated and so potentially increasing tolerability over direct NMDA receptor blockers.…”
Section: Discussionmentioning
confidence: 72%
“…Recent studies showed that endogenous nitric oxide (NO) can modulate the activity of high-threshold muscle afferents [12,13]. Nitric oxide synthase (NOS) is expressed in some spinal neurons; it can be activated in central neurons during the development of muscle fatigue [14].…”
Section: Introductionmentioning
confidence: 99%